1999
DOI: 10.1055/s-1999-2925
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective α-Alkylation of New Chiral Auxiliaries: An Access to Enantiomerically Pure α- and α,β-Substituted β-Amino Acids

Abstract: New bicyclic heterocycles 5, which are potentially useful for the enantioselective synthesis of substituted b-amino acids, have been synthesized. A study on the a-alkylation of these chiral auxiliaries is presented. An optically pure b-amino acid was obtained in excellent yield from its masked chiral derivative 6a.The asymmetric synthesis of b-amino acids 1 has attracted much attention in recent years 2 owing especially to their use as building blocks for the synthesis of b-lactam antibiotics. 3 We recently p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…We present here an efficient access to acyclonucleosides 4 and 6 starting from β-amino alcohols 1 in three high-yielding steps. Reaction of the β-amino alcohol with cyanogen bromide followed by condensation of the resulting heterocycle 2 with ethyl propiolate or ethyl butynoate led to pyrimidinones 3 (Scheme ) 1 …”
mentioning
confidence: 99%
“…We present here an efficient access to acyclonucleosides 4 and 6 starting from β-amino alcohols 1 in three high-yielding steps. Reaction of the β-amino alcohol with cyanogen bromide followed by condensation of the resulting heterocycle 2 with ethyl propiolate or ethyl butynoate led to pyrimidinones 3 (Scheme ) 1 …”
mentioning
confidence: 99%
“…We have already reported that synthons 2a react stereoselectively at the C-6 site of the uracil ring with different organocuprate reagents (Scheme ), leading to alkylated compounds 5 . These heterocycles eventually were transformed into pure β-amino acids 3 …”
Section: Resultsmentioning
confidence: 99%